Methodologies for Backbone Macrocyclic Peptide Synthesis Compatible With Screening Technologies - Shinbara, Koki; Liu, Wenyu; van Neer, Renier Herman Pieter; Katoh, Takayuki; Suga, Hiroaki (Frontiers in Chemistry, 2020)
Backbone macrocyclic structures are often found in diverse bioactive peptides and contribute to greater conformational rigidity, peptidase resistance, and potential membrane permeability compared to their linear counterparts. Therefore, such peptide scaffolds are an attractive platform for drug-discovery endeavors. Recent advances in synthetic methods for backbone macrocyclic peptides have enabled the discovery of novel peptide drug candidates against diverse targets. Here, we overview recent technical advancements in the synthetic methods including 1) enzymatic synthesis, 2) chemical synthesis, 3) split-intein circular ligation of peptides and proteins (SICLOPPS), and 4) in vitro translation system combined with genetic code reprogramming. We also discuss screening methodologies compatible with those synthetic methodologies, such as one-beads one-compound (OBOC) screening compatible with the synthetic method 2, cell-based assay compatible with 3, limiting-dilution PCR and mRNA display compatible with 4.